PERBEDAAN KEMAMPUAN KONEKSI MATEMATIK DAN BERPIKIR KREATIF DENGAN DISCOVERY LEARNING DAN DIRECT INSTRUCTION - samuel juliardi sinaga (Sepren, 2020)
ABSTRACT This study was conducted based on low connection mathematical and creative thinking ability of students. The aim of this study was to determine: (1) whether the connection mathematical of students use Discovery Learning is different than Direct Instruction, (2) whether the creative thinking abilities students Discovery Learning is different than Direct Instruction, (3) the student answers use Discovery Learning variatever than Direct Instruction, (4) to responses the students used Discovery Learning very positive. This study is a quasi experimental research. The study population was all students of class VII SMP Swasta Ampera Batang Kuis consisting of three parallel classes. Of all students in grade VII students of two classes selected for the sample. The experimental class were treated Discovery Learning and control class were treated Direct instruction. In this research has developed several learning tools such as lesson plan and student activity sheets. The instrument used to collect data in this study are: (1) test the ability of connection mathematical, (2) test the ability creative thinking of students. The tests were used is in the form of a description. The test has been declared valid and reliable by the reliability coefficient of 0.814 and 0.878. Descriptive analysis is intended to describe the students' answers. Inferential analysis of data was done by analysis of covariance (ANACOVA). The results showed that: (1) The ability of connection mathematical of students used Discovery Learning is different than Direct Instruction. This is evident from the results ANACOVA to F* = 14,559 is greater than Ftable = 4.052 with equation regression is for experiment class and for control class (2) The ability creative thinking of students is different than Direct Instruction. This is evident from the results ANACOVA to F* = 9,113 is greater than Ftable = 4.052 with equation regression is for experiment class and for control class (3) The process of student answers by using Discovery Learning assisted open ended better than Direct Instruction (4) to responses the students positive.